CORRELATION COMMUNICATION FACTOR WITH PATIENT SAFETY INCIDENTS - Orizani, Chindy Maria; Qomariah, Siti Nur; Iswati, Iswati (International Journal of Patient Safety and Quality, 2024)
Background: According to the seventh standard of hospital patient safety, effective communication is crucial for staff to ensure patient safety. Patient safety incidents can often be traced back to miscommunication, which can be avoided through clear and effective communication. The purpose of this research is to explain the correlation between communication factors and patient safety incidents at Hospital X. Method: The study utilized a cross-sectional design, employing purposive sampling to select 30 nurses working in the inpatient unit. The independent variables included communication among nurses, communication between nurses and doctors, communication between nurses and medical support departments, and communication between nurses and patients. The dependent variable was the occurrence of patient safety incidents. Data were gathered through observation and analyzed using the chi- square test, with a significance level set at p-value < 0.05. Result: The results showed that there was a correlation between interracial nurse communication with the patient safety incident (p-value = 0.001). There was a correlation between nurse and doctor communication with the patient safety incident (p-value = 0.000). There was a correlation between the communication nurse and the medical support department with the patient safety incident (p-value = 0.000). There was a correlation between nurse and patient communication with the   patient safety incident (p-value = 0.000). Conclusion: Nurses who possess strong and effective communication skills can help prevent patient safety incidents. To achieve this, it is essential to enhance knowledge about communication, provide training on patient safety, and ensure compliance among nurses with the implementation of standard operating procedures, along with support from hospital leadership in supervision.